APLIKASI PEMBERIAN GOLDEN HARVEST DAN RHIZOBIUM BERPENGARUH TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L.) - Asritanarni Munar; Dafni Mawar Tarigan; Ahmad Haris Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThis study to determine the effect of Golden Harvest fertilizer and Rhizobium on growth and production of soybean (Glycine max L.). Implemented using the design of Plots Divided  factorial with two factors. The results showed that administration of Golden Harvest Fertilizer real influence on plant height parameters (2 and 3 MST MST), the number of branch age (4 and 6 MST MST), the age of flowering, harvest age, number of pods per plant contains, dry weight of 100 seeds and production per plot, but did not differ significantly to the age of 5 MST plant height, number of branches MST ages 2 and 3, the number of root nodules and the number of pods. Provision of Rhizobium give significantly different results at age 3 parameters plant height and number of branches MST MST age 4, but different is not real high on the plant age (2 and 4 MST MST), the number of branch age (2, 3, and 6 MST), age flowering, harvest age, the number of root nodules, the number of pods contain, the number of empty pods, and production per plot. And interactions between Golden Harvest Fertilizer and Rhizobium give significantly different results to the parameters age plant height and number of branches 6 MST MST age 5, but different is not real high on the plant parameter 2 s / d 5 MST, the number of branches of the age of 2, 3, 4 and 6 MST, the age of flowering, harvest age, the number of root nodules, contains a number of pods, number of empty pods, and production per plot.Keywords: Rhozobium, Golden Harvest, growth, soybean production